Communicating a social agenda within HEIs: the role of the social enterprise mark. Issue 3 (27th July 2018) - Sutton, Emma; McEachern, Morven; Kane, Kevin
Abstract : Purpose: By using the lens of the social enterprise mark (SEM) accreditation which enables social enterprises to "prove" that the interests of people and planet are put before shareholder gain, this study aims to enhance the knowledge of how effectively the social agenda is communicated by higher education institutions (HEIs). Design/methodology/approach: By using a qualitative research design, this exploratory study uses a combination of both a focus group and in-depth interviews with HEI holders of the SEM. Findings: With a particular focus on University A, this study advances the knowledge around how social agendas and the role of the SEM in particular are used to communicate to HEI employees as a key stakeholder group. Research limitations/implications: At the time of this study, fewer SEM accredited HEIs existed, and therefore, the following conclusions are based upon a small select sample of HEIs that held the SEM. Further studies are needed to provide a more representative view of each university's use of and commitment to the SEM/ Social Enterprise Gold Mark. Practical implications: Building on Powell and Osborne's (2015 ) observations regarding the role of marketing in social enterprises, the findings of this study offer practical insight into current and or prospective HEI SEM holders as to the role of "social" accreditations, stakeholder perceptions of such marketing initiatives and how they can be used as a vehicle to improve social communications in the future. Originality/value: The area of social enterprise and social impact has been evolving in recent decades, but literature in relation to its promotion and communication in the higher education sector remains scant. This study responds to this gap in the literature by providing greater insight into how social agendas and engagement with the SEM, specifically, are communicated by HEIs.